1991
DOI: 10.1152/jappl.1991.71.1.328
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of hypophosphatemia in humans with heatstroke

Abstract: Hypophosphatemia is common in heatstroke, but little is known about its mechanism. We investigated 10 consecutive patients with heatstroke (mean age 58 +/- 2 yr) whose mean rectal temperature at admission was 42.3 +/- 0.2 degrees C. Eight patients presented with hypophosphatemia [0.48 +/- 0.08 mmol/l, normal range (NR) 0.8-1.4 mmol/l], associated with increased fractional excretion of phosphate (19.8 +/- 6.4%, NR 6-20%) relative to plasma phosphate levels and reduced renal threshold for phosphate (0.55 +/- 0.0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
13
0

Year Published

1995
1995
2015
2015

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(14 citation statements)
references
References 0 publications
1
13
0
Order By: Relevance
“…Sodium, potassium, calcium, and magnesium plasma concentrations are usually normal and hemoconcentration is uncommon with classic heat stroke (42,43). This is in contrast to exertional heat stroke where hyponatremia, hypocalcemia, hyperkalemia, and hypoglycemia may occur (189,348).…”
Section: Dehydration and Electrolyte Disturbancesmentioning
confidence: 99%
See 1 more Smart Citation
“…Sodium, potassium, calcium, and magnesium plasma concentrations are usually normal and hemoconcentration is uncommon with classic heat stroke (42,43). This is in contrast to exertional heat stroke where hyponatremia, hypocalcemia, hyperkalemia, and hypoglycemia may occur (189,348).…”
Section: Dehydration and Electrolyte Disturbancesmentioning
confidence: 99%
“…Thermal injury to the vascular endothelium is considered the primary event that initiates coagulation in heat stroke patients (41,47,260). In vitro heat exposure (43)(44) • C) was shown to activate platelet aggregation and cause irreversible hyperaggregation that persisted despite cooling (113,400). Treatment of cancer patients with whole body hyperthermia treatment at body temperatures as low as 39…”
Section: Hematologic Disturbancesmentioning
confidence: 99%
“…While some studies (11,45) have reported that acute hypophosphataemia and hypocalcaemia are observed in classical heat stroke and are probably related to the increased glucose phosphorylation seen in alkalotic conditions (22) a few authors (32,36) have noted hyperphosphataemia due to resultant rhabdomyolysis associated with sustained hyperthermia, hypoxia and hypoperfusion. Also, in some cases of heat stroke rhabdomyolysis may develop and muscle cells may be injured.…”
Section: Discussionmentioning
confidence: 99%
“…Rats were housed under controlled temperature (22 ± 1°C) and lighting conditions (07:00 to 19:00), with food and water made available ad libitum throughout the experiments. The rats were randomly divided into four groups: [1] the normal control, [2] diabetic control, [3] diabetic heatstroke, and [4] diabeticheatstroke-whole body cooling (WBC), with 8 rats in each group. Diabetes was produced by injecting streptozotocin (STZ) (Sigma, St. Louis, MO, USA) at 30 mg/kg in the tail veins.…”
Section: Animals and Treatmentmentioning
confidence: 99%
“…Multiorgan dysfunctions ensue from severe heatstroke, including hepatic and renal dysfunction, pulmonary and brain edema, hypotension, cerebral ischemia and injury, and activated inflammation. Currently, the treatment of heatstroke is whole body cooling (WBC) (4,11,19,24). In rats, WBC immediately after the onset of heatstroke reduced the heatstroke-induced circulatory shock, cerebral ischemia, neuronal damage, and surge of tissue ischemia and damage markers in the hippocampus, and resulted in prolongation of survival time (8).…”
Section: Introductionmentioning
confidence: 99%